2019
DOI: 10.1111/ajag.12666
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a method to estimate the point prevalence of cognitive impairment and delirium in a multi‐campus Australian health service

Abstract: Objective To design, test (pilot) and implement a study to estimate the point prevalence of cognitive impairment (CI) and delirium in a multi‐site health service. Methods Clinicians were trained to use the 4 A's Test (4AT) to screen for cognitive impairment and delirium, and the 3‐minute Diagnostic Interview for the Confusion Assessment Method (3D‐CAM) to detect delirium in those with abnormal 4AT results. Outcomes of interest were as follows: (a) rates of cognitive impairment and delirium and (b) feasibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…However, more information is needed about the accuracy of the 4AT in different ethnicities and languages. For instance, a previous study reported confusion among pilot surveyors when completing the 4AT in languages such as Mandarin, where numbers represent the months of the year [ 30 ]. A particular concern was the reliance on family interpreters despite the availability of professional interpreters for patients with limited English and deafness.…”
Section: Discussionmentioning
confidence: 99%
“…However, more information is needed about the accuracy of the 4AT in different ethnicities and languages. For instance, a previous study reported confusion among pilot surveyors when completing the 4AT in languages such as Mandarin, where numbers represent the months of the year [ 30 ]. A particular concern was the reliance on family interpreters despite the availability of professional interpreters for patients with limited English and deafness.…”
Section: Discussionmentioning
confidence: 99%